Market failures in the airport sector and counterposition of the neoclassic vision with the austrian school and public choice alternatives - Mazzoni, João Fernando Rossi (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2019)
The goal of the present work is to analyze the economic regulation issue applied to the airport sector, conciliating visions of three currents of economic thought on the subject. It will present the characteristics of the market failures in the neoclassical perspective, representative of the economic mainstream, and the problems of trying to regulate the sector from the perspective of two different schools of economic thought, focusing on the vision of the Austrian School of Economics and some insights of the Public Choice School.